2020
DOI: 10.1101/2020.04.04.022533
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Maternal Continuous Oral Oxycodone Self-Administration Alters Pup Affective/Social Communication but not Spatial Learning or Sensory-Motor Function

Abstract: The broad use and misuse of prescription opioids during pregnancy has resulted in a surge of infants diagnosed with Neonatal Opioid Withdrawal Syndrome (NOWS). Shortterm irritability and neurological complications are hallmarks of NOWS, but the longterm consequences are unknown. Our newly-developed preclinical model of oxycodone self-administration enables adult female rats to readily drink oxycodone (0.06-0.12 mg/ml, ~10/mg/kg/day) continuously before and during pregnancy and after delivery, to achieve simila… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…However, currently the literature on maternal care following Oxy exposure is conflicting. Two recent rodent studies found no changes in maternal behavior or maternal motivation following dam Oxy exposure ( Watters et al, 2020 ; Zanni et al, 2020 ). Notably, in our study, in utero Oxy exposed offspring demonstrated comparable USV means to Veh controls.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, currently the literature on maternal care following Oxy exposure is conflicting. Two recent rodent studies found no changes in maternal behavior or maternal motivation following dam Oxy exposure ( Watters et al, 2020 ; Zanni et al, 2020 ). Notably, in our study, in utero Oxy exposed offspring demonstrated comparable USV means to Veh controls.…”
Section: Discussionmentioning
confidence: 94%
“…The dosage of Oxy (Sigma-Aldrich, Saint Louis, MO, United States; Lot#: SLBX4974) administration was guided by previous literature with concentrations ranging from 0.5 to 33 mg/kg/day ( Enga et al, 2016 ; Sithisarn et al, 2017 ; Zanni et al, 2020 ). Based on this dosage range, we generated our own dosage curve through continuous Oxy administration to pregnant dams at 5, 10, or 15 mg/kg/day using the subcutaneous Alzet 2006 model pump (Durect Corporation, Cupertino, CA, United States; Lot #: 10376-17).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dosage of Oxy (Sigma-Aldrich, Saint Louis, MO; Lot#: SLBX4974) administration was guided by previous literature with concentrations ranging from 0.5 mg/kg/day to 33 mg/kg/day [19][20][21] . Based on this dosage range, we generated our own dosage curve through continuous Oxy administration to pregnant dams at 5, 10, or 15 mg/kg/day using the subcutaneous Alzet 2006 model pump (Durect Corporation, Cupertino, CA; Lot #: 10376-17).…”
Section: Drug Dosagementioning
confidence: 99%
“…Righting reflex was assessed at P14 as follows: each mouse was placed prone onto its abdomen and quickly pronated 180° to its back in a smooth motion. The time for the mouse to right itself with all four paws positioned underneath the abdomen was recorded 20 . Each mouse underwent three timed trials, which were averaged for analysis.…”
Section: Developmental Reflexes and Milestones Assessmentmentioning
confidence: 99%